Impact of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) on Earning Quality with Capital Structure as a Moderating Variable - Monic Anastasya Maryunda; Rina Trisnawati; Erma Setiawati (Journal Research of Social Science, Economics, and Management, 2023)
Purpose: This research aims to analyze the influence of Corporate Social Responsibility (CSR) disclosure, managerial ownership, board of commissioners, on earnings quality with capital structure as moderating variables. Managerial ownership and the board of commissioners are proxies for Good Corporate Governance (GCG). Methodology: This research used secondary data which can be accessed in the Indonesia Stock Exchange (IDX) website (www.idx.co.id). The sampling method used a purposive sampling technique and data processing in this research used SPSS 24 software. Results: The results of in this research show that disclosure of Corporate Social Responsibility (CSR), managerial ownership, and the board of commissioners had significant effect on earnings quality. Capital structure strengthens the relationship between Corporate Social Responsibility (CSR) disclosure and earnings quality. Besides that, capital structure strengthens the relationship between managerial ownership and earnings quality. The relationship between the board of commissioners and earnings quality is also strengthened by the capital structure. Applications/Originality/Value: The implication of this research which to improve earning quality, companies must disclose more Corporate Social Responsibility (CSR) and strengthen Good Corporate Governance (GCG) in managing the company so that the company can achieve its goals.